Unveiling the impact of Chlorella vulgaris supplementation on liver metabolisms of aged rats − A preclinical study - Ogechi Ekeuku, Sophia; Zainul Azlan, Nurhazirah; Mohd Yusof, Yasmin Anum; Tan, Jen Kit; Makpol, Suzana (Elsevier, 2024)
Chlorella vulgaris is renowned for its rich nutritional composition and has been associated with various health benefits. This study aimed to look into the effect of CV on liver metabolomes and metabolic pathways in aged Sprague Dawley (SD) rats. Three and 21-month-old male SD rats were divided into control and treated groups. Results showed that carbohydrates such as maltose/lactose and mannose/fructose were downregulated in old rats. These metabolites were downregulated in young rats supplemented with CV. Interestingly, taurine was upregulated in old rats, while the trend was reversed in old rats supplemented with CV at 300 mg/kg/d. The differentially expressed metabolites in different age groups and CV supplementation were mapped to starch and sucrose metabolism, galactose metabolism, and taurine and hypotaurine metabolism. Further research is needed to understand the long-term effects of CV supplementation on ageing and determine optimal dosage levels, especially regarding its potential to mitigate age-related diseases.